Absence of the ER Cation Channel TMEM38B/TRIC-B Disrupts Intracellular Calcium Homeostasis and Dysregulates Collagen Synthesis in Recessive Osteogenesis Imperfecta. - Wayne A Cabral; Masaki Ishikawa; Matthias Garten; Elena N Makareeva; Brandi M Sargent; MaryAnn Weis; Aileen M Barnes; Emma A Webb; Nicholas J Shaw; Leena Ala-Kokko; Felicitas L Lacbawan; Wolfgang Högler; et al. (PLoS Genetics)
Recessive osteogenesis imperfecta (OI) is caused by defects in proteins involved in post-translational interactions with type I collagen. Recently, a novel form of moderately severe OI caused by null mutations in TMEM38B was identified. TMEM38B encodes the ER membrane monovalent cation channel, TRIC-B, proposed to counterbalance IP3R-mediated Ca2+ release from intracellular stores. The molecular mechanisms by which TMEM38B mutations cause OI are unknown. We identified 3 probands with recessive defects in TMEM38B. TRIC-B protein is undetectable in proband fibroblasts and osteoblasts, although reduced TMEM38B transcripts are present. TRIC-B deficiency causes impaired release of ER luminal Ca2+, associated with deficient store-operated calcium entry, although SERCA and IP3R have normal stability. Notably, steady state ER Ca2+ is unchanged in TRIC-B deficiency, supporting a role for TRIC-B in the kinetics of ER calcium depletion and recovery. The disturbed Ca2+ flux causes ER stress and increased BiP, and dysregulates synthesis of proband type I collagen at multiple steps. Collagen helical lysine hydroxylation is reduced, while telopeptide hydroxylation is increased, despite increased LH1 and decreased Ca2+-dependent FKBP65, respectively. Although PDI levels are maintained, procollagen chain assembly is delayed in proband cells. The resulting misfolded collagen is substantially retained in TRIC-B null cells, consistent with a 50-70% reduction in secreted collagen. Lower-stability forms of collagen that elude proteasomal degradation are not incorporated into extracellular matrix, which contains only normal stability collagen, resulting in matrix insufficiency. These data support a role for TRIC-B in intracellular Ca2+ homeostasis, and demonstrate that absence of TMEM38B causes OI by dysregulation of calcium flux kinetics in the ER, impacting multiple collagen-specific chaperones and modifying enzymes.